Efforts and Models of Education for Parents: the Danish Approach - Dorthe Brix; Niels Rosendal Jensen (Social Work & Society, 2009)
The report examines the relationship between day care institutions, schools and so called "parents unfamiliar to education" as well as the relationship between the institutions. With in Danish public and professional discourse concepts like parents unfamiliar to education are usually referring to environments, parents or families with either no or just very restricted experience of education except for the basic school (folkeskole). The "grand old man" of Danish educational research, Prof. Em. Erik Jørgen Hansen, defines the concept as follows: Parents who are distant from or not familiar with education, are parents without tradition of education and by that fact they are not able to contribute constructively in order to back up their own children during their education. Many teachers and pedagogues are not used to that term; they rather prefer concepts like "socially exposed" or "socially disadvantaged" parents or social classes or strata. The report does not only focus on parents who are not capable to support the school achievements of their children, since a low level of education is usually connected with social disadvantage. Such parents are often not capable of understanding and meeting the demands from side of the school when sending their children to school. They lack the competencies or the necessary competence of action. For the moment being much attention is done from side of the Ministries of Education and Social Affairs (recently renamed Ministry of Welfare) in order to create equal possibilities for all children. Many kinds of expertise (directions, counsels, researchers, etc.) have been more than eager to promote recommendations aiming at achieving the ambitious goal: 2015 95% of all young people should complement a full education (classes 10.-12.). Research results are pointing out the importance of increased participation of parents. In other word the agenda is set for 'parents' education'.